Equity, Inclusive Education and Education for Social Justice. Do all Paths Lead to the Same Goal? - Cecilia Simón; Ángela Barrios; Héctor Gutiérrez; Yolanda Muñoz (Universidad Autónoma de Madrid, 2019)
The work presented is about contributing to reflection around synergies and differences between inclusive education, equity and education for social justice. When talking about an education for all people without exclusions, the starting point will be human rights, which has become an international challenge as reflected in the 2030 Agenda for Sustainable Development. A reference framework that is capable of guiding and evaluating the development of educational policies and practices is needed. The perspectives from equity, inclusive education and social justice can contribute to it. Special attention will be given to the consequences of the different discourses and ways of understanding inclusive education, to try to define who we are talking about when we talk about inclusion, what dimensions make it up, how its nature is and what place it should occupy in the transformation of Educational systems Different perspectives share principles and aspirations, and all of them are inspiring to build a common dialogue around what education we want.